The Influence of Stakeholder Pressure and Audit Quality on Sustainability Performance - Budi, Saksono; Kurniawati, Desi (IJESS International Journal of Education and Social Science, 2025)
The influence of stakeholder pressure and audit quality on sustainability performance. The purpose of this study is to examine the relationship between stakeholder pressure and Sustainability Performance, to examine the relationship between audit quality and Sustainability Performance. The research was conducted using associative quantitative methods. The type of data uses secondary data. The population in this study were Primary Consumer Goods Sector Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) index from 2017 to 2022 as many as 12 companies using the company's financial statements listed on theBEI. The sample determination method in this study used purposive sampling of 72 samples. The results of the study can be concluded that stakeholder pressure affects Sutainability Performance and Audit Quality affects Sutainability Performance. In this study also tested the variables of stakeholder pressure and audit quality together on Sutainability Performance Based on the test results, the variables of stakeholder pressure and audit quality together have an effect on Sutainability Performance. As a result of this research, it is suggested that companies should also attach importance to knowledge, expertise and innovation in the field of sustainability so as to give companies a competitive advantage in adopting and implementing sustainable practices. Accurate and transparent information about the company's sustainability efforts can also increase trust and support from stakeholders.